Effect of structural, magnetic, magnetocaloric, and electrical polarization properties for multiferroic double perovskite Lu2CoCrO6 compound - Chatterjee,S; Dutta,A; Das,I (Journal of Applied Physics, 2024)
We synthesized the Lu 2 CoCrO 6 compound, multiferroic member of double perovskite system, by sol-gel method and then investigated the crystal structure, magnetization, magnetocaloric effect (MCE), and electrical polarization study. The analysis of powder x-ray diffraction pattern confirms that the monoclinic crystal structure with P2 1 /n space group is better fitting for the Lu 2 CoCrO 6 compound. Distribution between Co and Cr ions at the B-site is not perfectly ordered. Partial ordering between these B-site cations leads to a certain degree of disorder due to the presence of antisite defects and antiphase boundaries. These anti-site disorders (in the B-site) generate various fascinating magnetic phenomena. Although the temperature dependent inverse susceptibility plot shows predominant antiferromagnetic ground state in this system, simultaneously, a second order magnetic phase transition was observed from the Arrott plot. Moreover, the isothermal magnetization study confirms the coexistence of antiferromagnetic (AFM) and ferromagnetic (FM) phases below the transition temperature. The investigation of the magnetocaloric effect shows that the AFM phase of the system converts into the FM phases above critical field values. However, the breakdown of universal behavior of MCE in the paramagnetic region confirms the coexistence of the AFM phase as a secondary phase within the FM matrix. In addition, at lower temperatures, we observe a clear and well-defined ferroelectric hysteresis loop, suggesting ferroelectricity in the material. From these results, we conclude that Lu 2 CoCrO 6 is a multiferroic material in which the coexisting magnetic and multiferroic phases appear to be correlated and weak magneto-electric coupling was also observed. Furthermore, our experimental results help to encourage basic fundamental as well as applied research on rare-earth and transition metal based double perovskite systems due to their complex exchange interaction and multiferroic beha